Screening and Identification of Novel cGAS Homologues Using a Combination of in Vitro and In Vivo Protein Synthesis - Rolf, Jascha (Int J Mol Sci, 2019)
The cyclic GMP-AMP synthase (cGAS) catalyzes the synthesis of the multifunctional second messenger, cGAMP, in metazoans. Although numerous cGAS homologues are predicted in protein databases, the catalytic activity towards cGAMP synthesis has been proven for only four of them. Therefore, we selected five novel and yet uncharacterized cGAS homologues, which cover a broad range in the field of vertebrates. Cell-free protein synthesis (CFPS) was used for a pre-screening to investigate if the cGAS genes originating from higher organisms can be efficiently expressed in a bacterial expression system. As all tested cGAS variants were expressible, enzymes were synthesized in vivo to supply higher amounts for a subsequent in vitro activity assay. The assays were carried out with purified enzymes and revealed vast differences in the activity of the homologues. For the first time, the cGAS homologues from the Przewalski’s horse, naked mole-rat, bald eagle, and zebrafish were proven to catalyze the synthesis of cGAMP. The extension of the list of described cGAS variants enables the acquisition of further knowledge about the structural and molecular mechanism of cGAS, potentially leading to functional improvement of the enzyme.